Synthesis and Diverse Transformations of a Dinitrogen Dititanium Hydride Complex Bearing Rigid Acridane‐Based PNP‐Pincer Ligands - Mo, Zhenbo; Shima, Takanori; Hou, Zhaomin (Angewandte Chemie International Edition, 2020)
Studies on N2 activation and transformation by transition metal hydride complexes are of particular interest and importance. The synthesis and diverse transformations of a dinitrogen dititanium hydride complex bearing the rigid acridane‐based acriPNP‐pincer ligands {[(acriPNP)Ti]2(μ2‐η1:η2‐N2)(μ2‐H)2} are presented. This complex enabled N2 cleavage and hydrogenation even without additional H2 or other reducing agents. Furthermore, diverse transformations of the N2 unit with a variety of organometallic compounds such as ZnMe2, MgMe2, AlMe3, B(C6F5)3, PinBH, and PhSiH3 have been well established at the rigid acriPNP‐ligated dititanium framework, such as reversible bonding‐mode change between the end‐on and side‐on/end‐on fashions, diborylative N=N bond cleavage, the formal insertion of two dimethylaluminum species into the N=N bond, and the formal insertion of two silylene units into the N=N bond. This work has revealed many unprecedented aspects of dinitrogen reaction chemistry. Ti, NN, Ti: A dinitrogen dititanium hydride complex bearing the rigid acridane‐based acriPNP‐pincer ligand undergoes diverse transformations with a variety of organometallic compounds. Many aspects of the dinitrogen reaction chemistry are thus revealed.